Analisis Kinerja Routing Protocol Low Power and Lousy Network Pada Contiki Cooja dengan Menggunakan Metode Time of Arrival - Putri Ayu Delina Sari; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Wireless Sensor Network (WSN) is a technology that develops very rapidly and causes it to be used on devices that we encounter everyday. All sensor nodes have various addresses and have the ability to retrieve, process and send data. Due to limited resources, WSN nodes have the ability to process and use energy consumption power which at each node is low, which makes the writer feel the need for RPL performance research, namely routing protocol specifically for low power radio and has the advantage that each node has processor power limited, low memory, low energy consumption on Contiki cooja simulator and low data rates. This study tested five scenarios, namely 10, 20, 30, 40 and 50 nodes with parameters of distance localization, routing overhead and packet delivery ratio. The test results show the influence of these parameters with the number of different nodes in a network. The localization test results show the results of testing where if the communication between client nodes and server nodes takes a long time, it can be seen that the distance between these nodes is getting farther away. The routing overhead test results show a trend of increasing values ​​as the number of nodes increases. In routing overhead testing using 10, 20, 30, 40 and 50 Nodes, respectively 64.58%, 72%, 72.93%, 73.01% and 75.56%. The results show that the more nodes on a network, the greater the Packet Delivery Ratio